Managerial and natural disposability in two-stage network structure: a DEA-based approach - Mahnaz Maghbouli; Azam Pourhabib Yekta (Big Data and Computing Visions)
The traditional Data Envelopment Analysis (DEA) model on network-structured performance analysis normally considers desirable intermediate measures. In many real cases, the intermediate measures consist of both desirable and undesirable factors. The motivation of this paper is employing “Natural and managerial disposability” in two-stage network structures with undesirable intermediate measure. The non-cooperative game theory is proposed to study the two-stage structure. A real case of 34 OECD countries in 2012 has been illustrated to shed a light on applicability of the proposed methodology.